Granulosa cell tumor of testis: Clinicopathological correlation of a rare tumor - Swapnil Ulhas Rane; Santosh Menon; Sangeeta Desai; Ganesh Bakshi; Amit Joshi (Wolters Kluwer Medknow Publications, 2014)
Background: Granulosa cell tumor of testis is a rare tumor accounting for less than 4% of adult testicular tumors though they account for nearly 30% of childhood testicular tumors. Due to the rarity of these tumors, exact etiology, pathogenesis, prognostic factors and best treatment approach are not well known. The molecular events in pathogenesis of these stromal tumors have begun to unravel and these developments put forth a reasonable and scientific explanation for the association of these tumors with developmental anomalies like undescended testis. However, many questions remain unanswered. Materials and Methods: We performed a retrospective analysis of clinicopathological features of all Granulosa Cell Tumors of testis from our archives in addition to an extensive literature search using PUBMED with the key words "Granulosa Cell Tumor, testis". Results: We found six cases in our archives, two of which were of juvenile type and four of adult type. One out of these six cases presented with metastases. All cases underwent radical orchidectomy. Morphology and immunohistochemistry were classical in all cases and there was no diagnostic dilemma. Literature search revealed 63 cases of testicular Granulosa Cell Tumor in addition to highlighting the similarities in the biology and the dissimilarities in the clinical behavior as compared to ovarian Granulosa Cell Tumor. Conclusion: Testicular Granulosa Cell Tumor is a rare tumor, which although histologically similar to its ovarian counterpart, differs in clinical behavior. Further detailed investigations are needed to reveal the mystery behind the differing clinical behavior despite histological and immunohistochemical similarity between the testicular and ovarian Granulosa Cell Tumors.